Spillovers of quantitative easing on financial markets of Thailand, Indonesia, and the Philippines - Pathairat Pastpipatkul (2018)
© Springer International Publishing Switzerland 2015. This paper provides the results of the effectiveness of the quantitative easing (QE) policy, including purchasing mortgage-backed securities, treasury securities, and other assets in the United States, on the financial markets of Thailand, Indonesia, and the Philippines (TIP) in the post-QE introduction period. In this study, we focused on three different financial markets, which include the exchange rate market, stock market, and bond market. We employed a Bayesian Markov-switching VAR model to study the transmission mechanisms of QE shocks between periods of expansion in the QE policy and turmoil with extraordinarily negative events in the financial markets and the global economy. We found that QE may have a direct substantial effect on the TIP financial markets. Therefore, if the Federal Reserve withdraws the QE policy, the move might also have an effect on the TIP financial market. In particular, purchasing the mortgage-backed securities (MBS) program is more likely to affect the TIP financial markets than purchasing the other programs.